Clinical study of open versus laparoscopic management for gastroduodenal perforation - Ullah, Sami; Uddin, Warda Mohay; Iqbal, Zafar; Ullah, Irfan; Iqbal, M. Asad; Jie, Wang; Sun, Wang; Dong, Tong; Daorong, Wang (International Journal of Research in Medical Sciences, 2017)
Background: This study was organized to compare the clinical efficacy of laparoscopic and open repair of gastroduodenal perforation, and to provide the impressive surgical method of treatment for gastroduodenal perforation. Methods: The present study was conducted with 174 consecutive patients treated for gastroduodenal perforations. These patients included 121 with perforated gastric ulcers, 53 with perforated duodenal ulcers, Whereas 31 patients were treated laparoscopically, and 143 patients underwent conventional (open) surgery. Results: A total of 174 patients were studied with men and women ratio of 4:1. This observational study revealed 80% male preponderance, with mean age of 48 years. Gastric perforations (n=77, i.e., 84.62%) were more common than duodenal perforations (n=14, i.e., 15.38%). Simple closure with omental patch (n=74, i.e., 81.32%) was the most common surgical method for duodenal perforation. While for gastric perforations were repaired primarily with two layered sutures. The mean operating time of open were 61 min and 86 min for laparoscopic surgery. Wound infection was the commonest post-operative complication which was seen in 31 (17.81%) patients. Conclusions: Laparoscopic gastroduodenal perforation repair is safe and reliable, has good clinical efficacy, the incidence of complications compared with open surgery does not increase, and has less surgical trauma, less bleeding, advantages of fast recovery of gastrointestinal function and short hospitalization time, Thus it has great clinical significance and should be promoted in surgery.